The Experience Economy in Shaping the Competitiveness of Tourist Regions - Gryszel, Piotr (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2018)
Contemporary tourist attractions that McDonaldsize and Disneyize the product they offer tourists are very well-received and are often the main reason tourist trips are taken. Thus, they significantly boost the competitiveness of their regions’ tourism. Based on an examination of the subject literature and surveys of tourists visiting the Sudety Mountain as a tourist region, the article assesses the impact of contemporary tourist attractions, creating the experience of tourists, on the competitiveness of the tourist region. The analysis included entries, evaluations and statements expressed in TripAdvisor’s app, and referring to tourist attractions located in the tourist region studied. The contemporary approach associated with the experience economy is one of the most effective tools for creating the competitive position of the Sudety tourist market.